2016
DOI: 10.1002/2016gl069480
|View full text |Cite
|
Sign up to set email alerts
|

Observed eddy dissipation in the Agulhas Current

Abstract: Analyzing eddy characteristics from a global data set of automatically tracked eddies for the Agulhas Current in combination with surface drifters as well as geostrophic currents from satellite altimeters, it is shown that eddies from the Mozambique Channel and south of Madagascar dissipate as they approach the Agulhas Current. By tracking the offshore position of the current core and its velocity at 30°S in relation to eddies, it is demonstrated that eddy dissipation occurs through a transfer of momentum, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 32 publications
5
22
0
Order By: Relevance
“…These findings are in agreement with previous investigations which have shown that the characteristics of eddies within the region are well described by altimetry data [8,9,33], and the properties of the MB eddy, as well as the interactions with surrounding eddies, are similar to those defined in existing literature [3,[6][7][8][9][10][11]. Our observations also agree with a more recent study that demonstrated the dissipation of eddies upon reaching the Agulhas Current due to eddy-current interactions [34].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with previous investigations which have shown that the characteristics of eddies within the region are well described by altimetry data [8,9,33], and the properties of the MB eddy, as well as the interactions with surrounding eddies, are similar to those defined in existing literature [3,[6][7][8][9][10][11]. Our observations also agree with a more recent study that demonstrated the dissipation of eddies upon reaching the Agulhas Current due to eddy-current interactions [34].…”
Section: Discussionsupporting
confidence: 93%
“…The distribution of eddy birth points is similar to a previous study (Figure b of Braby et al, ), and the majority of the observed and simulated eddies passing through north of the Natal Bight is from the SEMC (Figure ). It is found that in the AVISO (OFES), 33 (40) eddies originate from the SEMC, while 5 (15) eddies are from the MC (Table ).…”
Section: Sources Of the Natal Pulsesupporting
confidence: 85%
“…In‐situ observations support the idea that barotropic instability due to the horizontal shear of the Agulhas Current plays a major role in the formation of the Natal Pulse (Elipot & Beal, ). Also, several studies reported the periodicity and evolution of the Natal Pulse (Rouault & Penven, ), and the role of cyclonic eddies on the strength of meanders (Braby et al, ). Although many efforts have been devoted to modeling of the Agulhas Current, recent sophisticated ocean models still exaggerate eddy activities offshore of the Agulhas Current core (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first simulation experiment is forced by absolute winds; the second is forced by relative winds (the wind speed relative to the surface current speed). It is anticipated that through the process of “mechanical damping,” a reduced EKE would enable a more accurate representation of cyclonic and anticyclonic eddy dynamics in the source region of the Agulhas Current (a different region to the study by Renault, Molemaker, Mcwilliams, et al, , which focuses on the simulation of eddies in the California Upwelling System) and that the eddy‐current dissipation processes shown by Braby et al () would be better simulated in the regional HYCOM. In addition to this, a detailed investigation of the eddy field in the source region of the Agulhas Current is undertaken.…”
Section: Introductionmentioning
confidence: 99%